2008
DOI: 10.1016/j.drugalcdep.2008.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Smoking tobacco along with marijuana increases symptoms of cannabis dependence

Abstract: Using tobacco with marijuana - smoking blunts and "chasing" marijuana with tobacco - contributes to cannabis dependence symptoms. Treatment for cannabis dependence may be more effective it addresses the issue of concurrent tobacco use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(122 citation statements)
references
References 32 publications
6
112
0
4
Order By: Relevance
“…This result was consistent with our first hypothesis, a), which supposed that the severity of polydrug dependence is most common with SPU rather than with non/occasional SPU. This result replicated those reported for alcohol and cannabis co-use [13][14][15], tobacco and cannabis co-use [16,17], and alcohol and tobacco co-use [18,19], even these results did not specifically focused on SPU.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This result was consistent with our first hypothesis, a), which supposed that the severity of polydrug dependence is most common with SPU rather than with non/occasional SPU. This result replicated those reported for alcohol and cannabis co-use [13][14][15], tobacco and cannabis co-use [16,17], and alcohol and tobacco co-use [18,19], even these results did not specifically focused on SPU.…”
Section: Discussionsupporting
confidence: 80%
“…Others studies have shown that simultaneous use of tobacco and cannabis increased the risk of cannabis abuse and dependence [16,17]. Studies dealing with alcohol and tobacco co-use have shown that current smoking status predicts alcohol dependence [18,19], but these studies did not focus specifically on simultaneous use of alcohol and tobacco.…”
Section: Introductionmentioning
confidence: 99%
“…The use of other routes of administration such as smoke-free vaporisers have the potential of reducing the harmful effects the smoke poses to the user as well as reducing tobacco consumption 74 . This may be particularly important as tobacco increases the addictive potential of cannabis [75][76][77] . Furthermore, tobacco use may be an independent risk factor for psychosis 78 , as well as modifying the risk from cannabis use 79 .…”
Section: Making Cannabis Safermentioning
confidence: 99%
“…Specifically in regard to cigarette smoking, this is a concern, as concurrent use of marijuana and tobacco is associated with increased symptoms of cannabis dependence [34]. Additionally, both cigarette and marijuana smoke contain carcinogenic compounds [35], which could result in increased health risks.…”
Section: Discussionmentioning
confidence: 99%